Konsep Pendekatan Behavior dalam Menangani Perilaku Indisipliner pada Siswa Korban Perceraian - Muchamad Agus Slamet Wahyudi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This present study aims to investigate the concept of a behavioral approach in handlingstudents’ indiscipline as a result of their parents’ divorce. It is one of approaches inguidance and counseling to change maladaptive behavior into adaptive one. Thebehavioral approach is deemed appropriate to deal with the students’ indiscipline atschool so as to have good behavior. The students’ indiscipline is due to the students’internal factor, including their family background in terms of a divorce case. Aqualitative descriptive approach was employed in this field research. The resultspromote that if assessment was done, planning could be expanded on the process of counseling. It started from the contract of counseling and went up to relaxation,modeling, rewards and punishment, as well as a follow-up phase.